Perkembangan Hadis Periode Pra-Pembukuan Hingga Pembukuan: Analisis Historis Ulama Kontemporer Muhammad Musthafa Azami - Asep Saepullah (Matan : Journal of Islam and Muslim Society, 2021)
Abstract: Hadis has undergone several phases in the history, from pre-canonical until today. This paper discussed the development of Hadis in pre-canonical and canonical era through the historical analysis of Muhammad Musthafa Azami. This study aims to obtain the transformation, the conclusion, and the authenticity of the historical development of pre-canonical and canonical in response to the orientalists doubts regarding the Hadis. This research is a library research with the primary data are the work of Muhammad Mustafha Azami. Data were collected by documentation and presented descriptively. The results showed that in the Prophet era, there were still few Muslims who could write properly and correctly, resulting the writing of Hadis was not popular since the Companions has focused on writing the Quran. However, some latest Companion and Tabi’in has begun to write and collect the scattered Hadis sheets slightly. Thus, according to Muhammad Mustafa Azami, the accusations of the orientalists regarding the Hadis as the Muslims’ creations is incorrect and misleading the history.